Effect of an Antimicrobial Stewardship Intervention on Outcomes for Patients with Clostridium difficile Infection - Welch, Hanna (Am J Infect Control, 2016)
BACKGROUND: Treatment of Clostridium difficile infection (CDI) is an ideal target for antimicrobial stewardship programs (ASP), as ASPs have been effective in improving care in patients with a variety of infections. Unfortunately, studies to date have not rigorously evaluated the impact of ASP involvement on complications attributed to CDI. METHODS: We performed a quasi-experimental study of adult patients with CDI prior to (n=307) and after (n=285) a real-time ASP review was initiated. In the ASP intervention group, a pharmacist member of the ASP was notified in real time of positive CDI results and consulted with the care team to initiate optimal therapy, minimize concomitant antibiotic and acid-suppressive therapy, and recommend surgical/infectious diseases (ID) consultation in complicated cases. The primary outcome was a composite of 30-day mortality, ICU admission, colectomy/loop ileostomy, and recurrence. A blinded review panel of ID physicians determined whether outcomes were attributed to CDI. RESULTS: A significantly higher percentage of patients in the ASP intervention group had acid-suppressive therapy discontinued (24% versus 9%, P=0.001), and, in patients with severe disease, significantly more patients in the ASP intervention group received an ID consult (17% versus 10%, P=0.035), received appropriate therapy with oral vancomycin (87% versus 59%, P<0.0001), and vancomycin therapy was initiated earlier (mean 1.05 days vs. 1.70 days, P=0.04), compared to the pre-intervention group. The incidence of the composite outcome was not significantly different between the ASP intervention and pre-intervention groups (12.3% versus 14.7%, P=0.40). CONCLUSIONS: ASP review and intervention in patients with CDI improved process measures. A decrease in composite outcomes was not found, which may be due to low baseline rates of attributable surgery (0–2%), mortality (2–3%) and ICU admission (4–6%) in our institution.